The Interpretation of Paṭirūpadesa in Contemporary Buddhist Sermons and Scriptures - Inthanon, Natthapol; Tansrisook, Sompornnuch (Journal of Buddhist Studies Chulalongkorn University, 2025)
Patirūpadesavāsa, meaning "dwelling in a suitable country," is an important term from the Pali Tipiṭaka, with later commentarial explanations describing the characteristics of a country where people can prosper. This article examines the meaning of patirūpadesa in the Maṅgalavisésakathā, contemporary Buddhist sermons, and Thai texts explaining Buddhist teachings. Additionally, it explores different approaches to interpreting Buddhist teachings through an analysis of this term. The study identifies three main interpretative approaches to patirūpadesa: (1) those who strictly adhere to commentarial explanations, (2) those who follow the commentaries but supplement them with their own perspectives, and (3) those who provide independent interpretations. These three groups include both those that use Thailand as an example and those that do not, reflecting three distinct methods of explanation: commentary-based, non-commentary-based, and Thailand-based exemplification. Although the commentarial tradition continues to influence interpretations of patirūpadesa due to its established role in Buddhist education, the Maṅgalavisésakathā by Prince Patriarch Vajirananavarorasa has significantly shaped later Thai-language interpretations of patirūpadesavāsa. His definition of patirūpadesa does not necessarily link it to the flourishing of Buddhism. Furthermore, his identification of Thailand as an example of patirūpadesa, with an analysis emphasizing the role of the monarchy in creating a suitable country, reflects nationalist and royalist perspectives in this interpretation. Keywords: Paṭirūpadesa, Mangalavisésakathā, Interpretation